2012
DOI: 10.1128/aac.01205-12
|View full text |Cite
|
Sign up to set email alerts
|

Herb-Drug Interaction between Echinacea purpurea and Etravirine in HIV-Infected Patients

Abstract: The aim of this open-label, fixed-sequence study was to investigate the potential of the botanical supplement Echinacea purpurea to interact with etravirine, a nonnucleoside reverse transcriptase inhibitor of HIV. Fifteen HIV-infected patients receiving antiretroviral therapy with etravirine (400 mg once daily) for at least 4 weeks were included. E. purpurea root/extract-containing capsules were added to the antiretroviral treatment (500 mg every 8 h) for 14 days. Etravirine concentrations in plasma were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…This new formulation will facilitate dosing and, consequently, patient acceptance and satisfaction. In addition, plasma concentrations of etravirine, administered once daily dissolved in water, were in the same range to those observed in subjects receiving undispersed etravirine tablets [11][14]. As well, all patients showed etravirine concentrations above the protein-binding adjusted 50% effective concentration 4 ng/mL.…”
Section: Discussionsupporting
confidence: 69%
“…This new formulation will facilitate dosing and, consequently, patient acceptance and satisfaction. In addition, plasma concentrations of etravirine, administered once daily dissolved in water, were in the same range to those observed in subjects receiving undispersed etravirine tablets [11][14]. As well, all patients showed etravirine concentrations above the protein-binding adjusted 50% effective concentration 4 ng/mL.…”
Section: Discussionsupporting
confidence: 69%
“…The results of the study were not clinically significant [109]. In a similar study, the use of echinacea did not effect etravirine concentrations in HIVinfected individuals [110].…”
Section: Cam Products Thought To Interact With Arv Therapysupporting
confidence: 56%
“…Similar to lopinavir studied by Penzak et al, no significant interaction has been found with darunavir [19]. Also no significant treatment effects were observed for any of the primary pharmacokinetic parameters after administration of etravirine with or without E. purpurea [20]. Already in 2007, Raner et al evaluated the potential of 11 isolated alkamides and a 33% and 95 % ethanolic E. purpurea root extract to inhibit cytochrome P450 2E1 in human liver microsomes and from an in vitro expression system.…”
Section: Pharmacokinetic Interactionsmentioning
confidence: 90%
“…A number of in vitro and in vivo studies suggest a potential for herb-drug interaction between different uncharacterized Echinacea extracts and the cytochrome P450 family of drug metabolizing enzymes (CYP 3A4, 2D6, 1 A2 and 2C9) [14][15][16][17]. But only the recently published pharmacokinetic drug interaction studies determined the influence of chemically characterized Echinacea preparations on CYP3A and CYP2D6, with four conducted in human [18][19][20][21] and seven in vitro studies [22][23][24][25][26][27].…”
Section: Pharmacokinetic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation